High-current low-energy electron beam generation in plasma system - Agafonov, A.V.; Bogachenkov, V.A.; Krastelev, E.G. (Вопросы атомной науки и техники, 2006)
Results of experimental investigations of low-energy high-current electron beam generation in a plasma-filled diode with a long plasma anode and an explosive emission cathode are given. An additional low-current electron beam was used to form the long plasma anode by means of the residual or prefilled gas ionization. The long anode is used simultaneously as the transportation channel with predictable parameters of plasmas. Low-current additional beam is emitted from the thermionic cathode, which can have different geometric form. The solution developed provides to create radial profiled plasmas channels of desired plasmas density distribution with a high reproducibility. Приведены результаты экспериментов по генерации низкоэнергетического сильноточного электронного пучка в плазмонаполненном диоде с протяженным плазменным анодом. Для создания протяженного плазменного анода, одновременно представляющего собой и канал для транспортировки пучка, используется ионизация напущенного в систему газа вспомогательным слаботочным пучком электронов. Для генерации сильноточного пучка используются различные «взрывоэмиссионные» катоды. Создание плазмы вспомогательным электронным пучком, эмиттируемым с термокатода (энергия в сотни электронвольт при токе в единицы ампер), форма которого может варьироваться, позволяет формировать плазменные каналы с различным поперечным профилем с высокой воспроизводимостью. Наведено результати експериментів по генерації низькоенергетичного потужнострумового електронного пучка в плазмозаповненому діоді із протяжним плазмовим анодом. Для створення протяжного плазмового анода, що одночасно є каналом для транспортування пучка, використається іонізація напущеного в систему газу допоміжним слабкострумовим пучком електронів. Для генерації потужнострумового пучка використаються різні "вибухоемісійні" катоди. Створення плазми допоміжним електронним пучком, що емітується з термокатода (енергія в сотні електронвольт при струмі в одиниці амперів), форма якого може варіюватися, дозволяє формувати плазмові канали з різним поперечним профілем з високою відтворюваністю.